Treatment of unipolar affective disorders in pregnant women - benefits and risks - Julia Pałuchowska; Anna Szymkowicz; Sara M. Rosołowska-Żak; Maria Sambura; Patrycja Paschke; Igor P. Miczek (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Mental disorders are becoming an increasingly common health condition in society worldwide, significantly affecting pregnant women as well. According to the latest research, 1.5 million people in Poland and as many as 350 million people worldwide suffer from depression. It has also been established that the problem affects as much as 10.5% of women across Europe. An increased risk of developing affective disorders is noted in the age group between 18 and 44 years, which is the population of women of reproductive age. The medical community faces the dilemma of implementing treatment that ensures the safety of the child during medication intake, while also considering the consequences of discontinuing treatment related to withdrawal effects of psychotropic substances and the potential for relapse of symptoms in women. The aim of the study was to review and summarize methods of treating depressive disorders in pregnant women, as well as to assess the benefits and risks associated with undertaking various therapeutic treatments. A review of scientific publications published in English and Polish was conducted using the PubMed and Google Scholar databases. Keywords such as "depression" and "pregnancy" were used. The treatment of depressive disorders in pregnant women remains a controversial topic and requires an individualized approach to each patient. During therapy, the potential benefits of pharmacological treatment, which carries the risk of complications for the fetus, and the choice of less invasive non-pharmacological methods should be considered. The diagnostic process and choice of further management should also include the potential risks associated with not treating unipolar affective disorder in pregnant women.